Martin Heidegger : key concepts (Acumen, 2010)
Heidegger's writings are among the most formidable in recent philosophy. The pivotal concepts of his thought are for many the source of both fascination and frustration. Yet any student of philosophy needs to become acquainted with Heidegger's thought. "Martin Heidegger: Key Concepts" is designed to facilitate this. Each chapter introduces and explains a key Heideggerian concept, or a cluster of closely related concepts. Together, the chapters cover the full range of Heidegger's thought in its early, middle, and later phases.